Correlates for Suicidality Among At-risk Youth Receiving Community-Based Mental Health Services - Celedonia Karen L; Karukivi Max; Abio Anne; Valenti Michael W; Wilson Michael L (SPRINGER, 2022)
"At-risk" adolescents are at high risk of unsuccessfully transitioning into adulthood and are also at elevated risk for suicidal behavior. Though much research has been conducted on risk factors for suicidality among the general adolescent population, research on suicidality among "at-risk" adolescents is lacking. This is a notable gap in the literature given that "at-risk" adolescents may be three times more likely to exhibit suicidality. The present study addressed this research gap by examining correlates for suicidality among "at-risk" adolescents receiving mental health services in the community. Using Electronic Health Record (EHR) data, risk factors for suicidality were analyzed at the bivariate and multivariate levels. Sexual abuse was a significant predictor of suicidality, as well as impulsivity for suicide attempt only. These findings may serve as useful adjuncts in the design of suicidality-screening tools and follow-up practices within the context of community-based mental health organizations which target at-risk adolescents.